(untitled) (Global Journal of Computer Science and Technology, 2013)
Software reliability engineering techniques focus on development and maintenance of software systems. This paper presents a improved component model. The model is used to estimate the reliability of software systems and the usage ration of each component. A component impact analysis which helps in focusing of testing is presented .The proposed method exhibits considerable improvement when compared against conventional methods.